Kyrgyz Republic : Request for a Three-Year Arrangement Under the Extended Credit Facility. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses the Kyrgyz Republic's Request for a Three-year Arrangement Under the Extended Credit Facility (ECF). Performance under the previous ECF arrangement, which expired last July, was good. Macroeconomic stability was restored, fiscal consolidation was stronger than planned, monetary policy was enhanced through a new interest rate-based framework, and supervision was strengthened in the financial sector. Although performance under the last ECF arrangement was good, new challenges have emerged, and some key reforms have yet to be implemented. The IMF staff supports the authorities' request for a three-year arrangement under the ECF.